Finite-time annular domain stability of impulsive switched systems: mode-dependent parameter approach. Issue 6 (3rd June 2019) - Gao, Lijun; Luo, Fangmei; Yan, Zhiguo
ABSTRACT: This paper investigates the finite-time stability of impulsive switched systems. By applying mode-dependent parameter approach and average impulsive switched interval technique, the conditions that guarantee the finite-time annular domain stability and finite-time annular domain boundedness for general linear and nonlinear impulsive switched systems are established. Meanwhile, the superiority of mode-dependent parameter approach over common parameter approach is analysed. Also, we consider the effect of different impulsive strengths and draw a less conservative conclusion. Moreover, we extend the conclusion from nonlinear impulsive switched systems to linear impulsive switched systems, and a new sufficient condition for state feedback controllers is proposed on the basis of coupled matrix inequalities. Furthermore, for systems containing external disturbance, we obtain a sufficient condition of finite-time annular domain boundedness. Finally, we present two examples to illustrate the effectiveness of the results.